Antibiotic use on small- and medium-sized pig farms – farmers’ knowledge and practices in North-eastern Thailand - Antibiotic use practises among Thai pigfarmers - Magnusson, Ulf (Swedish University of Agricultural Sciences, 2020)
The data was collected in October to December 2018 through structured interviews with farmers on small- and medium-sized pig farms in Khon Kaen province in northeastern Thailand. Small farms were categorized as farms keeping less than 50 sows while medium farms kept between 100 to 500 sows. The questionnaire contained both multiple-choice and open-ended questions. Answers were recorded using the open-source smartphone platform Open Data Kit (ODK) and were further exported to Microsoft Excel. In total, 164 pig farmers were interviewed. Each farmer was informed about the purpose of the study and that their answers would be anonymous. All farmers gave their consent to participate in the study before the interview. The main purpose was to collect data on antibiotic usage on pig farms of different level of intensification (i.e. small and medium) and on farmers’ knowledge regarding antibiotic use and resistance.

Data collected by interviews entered in ODK (Open Data Kit) and retrieved in Microsoft Excel.

Datamaterialet samlades in i Oktober till December 2018 genom strukturella intervjuer med grishållare på små och medelstora grisgårdar i Khon Kaen-provinsen i nordöstra Thailand. Små gårdar kategoriserades som gårdar med färre än 50 suggor medan medelstora gårdar hade mellan 100 och 500 suggor. Frågeformuläret innehöll både flervalsfrågor och öppna frågor. Svaren samlades in med hjälp av mobilapplikationen Open Data Kit (ODK) och exporterades sedan till Microsoft Excel. Sammanlagt intervjuades 164 grishållare. Alla som intervjuades informerades om syftet med datainsamlingen och att deras svar skulle vara anonyma och alla gav sitt medgivande innan intervjun påbörjades. Det huvudsakliga syftet med datainsamlingen var att samla in data om antibiotikaanvändning på grisgårdar av olika intensitetsgrad (d.v.s. små och medelstora) och om grishållarnas kunskap om antibiotikaanvändning och antibiotikaresistens.

Data från intervjuer samlades in genom Open Data Kit (ODK) och exporterades sedan till Microsoft Excel.
Antibiotikaanvändning på små och medelstora grisgårdar – grishållares kunskap och agerande i nordöstra Thailand - Antibiotikaanvändning bland thailändska grishållare
Keywords: Drug Resistance, Microbial; Resistens mot antimikrobiella läkemedel; pig farms; grisgårdar; Thailand; Thailand; Antimicrobial resistance; Antibiotika resistens; Veterinary Science; Veterinärmedicin; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin